No "Slippery Slope"? An Empirical Case Study on the Effect of Secular Science Textbooks on Student Religiosity in a Christian Private School. Issue 1 (2nd January 2016) - Reichard, Joshua D.
ABSTRACT: In context of legal battles over science textbooks in both public and private schools, this empirical case study examines student religiosity scores over a 3-year period following a school-wide curricular change from Christian-published to secular science textbooks in a K-12 Christian private school. The study found no statistically significant change in student religiosity scores for two subscales (organizational and non-organizational religiosity; p  = .799, p  = .232, respectively); however, for the third subscale, intrinsic religiosity, a statistically significant increase in student religiosity was reported ( p  ≤ .001). The study suggests that the curricular change had no discernible negative affect on student religiosity scores. Moreover, the study suggests that Christian private schools may utilize secular science textbooks and remain faithful to their religious missions, especially when coupled with teacher training in faith-learning integration.